Flow Cytometric Detection of Activated Platelets in Pregnant Women Prior to the Development of Pre-Eclampsia - Janes, Sarah L; Kyle, Phillipa M; Redman, Christopher; Goodall, Alison H (Thrombosis and Haemostasis, 1995)
Pre-eclampsia is a common complication of pregnancy, in which platelets may have an early pathogenetic role. In this prospective study a whole blood flow cytometric method has been used to detect circulating activated platelets in pregnant women prior to the development of pre-eclampsia. Activated platelets were identified by bound fibrinogen or by CD63 antigen expression. Of 121 healthy primiparous women studied at 28 weeks of pregnancy, 18 (15%) developed clinical pre-eclampsia six to thirteen weeks later. The platelets of these women showed increased fibrinogen binding ex vivo (5.1% platelets positive, compared with 3.4% in those who completed a normal pregnancy, p <0.02), and increased CD63 antigen expression (0.73% positive compared to 0.45%, p = 0.01). In contrast, no differences between the women with different outcomes were detected at 28 weeks in platelet counts, or plasma ß-thromboglobulin levels. These findings confirm that whole blood flow cytometry is a sensitive technique for investigating platelet activation in a clinical setting and support the hypothesis that platelets have a critical role in the pathogenesis of pre-eclampsia